Diaphragm muscle structure in the elderly: Findings from an autopsy study - Baptista Nucci, Ricardo Aparecido; Souza, Romeu Rodrigues de; Suemoto, Claudia Kimie; Busse, Alexandre Leopold; Mesiano Maifrino, Laura Beatriz; Anaruma, Carlos Alberto [UNESP]; Pasqualucci, Carlos Augusto; Jacob-Filho, Wilson (Elsevier B.V., 2020)
Sarcopenia is characterized as aging-related weakness and atrophy, which decreases the diaphragm force generating capacity leading to a decrease of expulsive non-ventilatory motor behaviors, which are critical for airway clearance. Thus, this study aimed to analyze the histopathology of the diaphragm in postmortem samples. Thirty individuals were included. Diaphragm samples were stained with hematoxylin and eosin for histopathological analysis. Picrosirius stain was used to highlight the collagen fibers. We observed a positive association between advancing age and histopathological findings in the diaphragm structure. We suggest that age is a key factor in increasing diaphragm muscle histopathology. However, further clinicopathological studies are needed to confirm our findings.
Keywords: Autopsy study; Aging effect; Diaphragm muscle; Histopathological analysis